Visual and instrumental evaluation of reliability of clinical ceramic restoration with dental shade guide by two distinct observer population: An observational study - Dolly Gupta (Indian Journal of Health Sciences and Biomedical Research KLEU, 2017)
Context: Dental ceramics are the most natural appearing replacement material for missing tooth substance available in a range of shades and translucencies to achieve a life-like result. Ceramic restorations are fabricated with porcelain layers of different opacity, shade, and thickness to provide a natural appearance. Since the ceramic layer thickness is important for shade development, utmost precision and control are required for a predictable and reproducible result. Shade guides provided by various companies are of 2.5 mm thickness, but clinically all-ceramic crown restoration requires a maximum thickness of 1.5 mm. Aim: The purpose of this study was to evaluate the shade of clinical ceramic restorations with dental shade guide by two distinct observer population. Materials and Methods: A total of 400 individuals aged 23-45 years participated in this observational study. Two hundred were dental professionals (DPs) and other 200 were nonprofessionals (NPs), a random passerby in the vicinity of the dental school. Evaluation was done between a shade guide and ceramic restorations of thickness 1.5 mm. For visual evaluation, observers were asked to take one shade tab from a box containing eight shades and to select the matching clinical ceramic restoration, and a number of correctly matched shades were recorded. Same experiment was repeated after 1 month for half of the observers. For instrumental evaluation, spectrophotometer was used, and three readings were taken per sample. Results: The results from the present study showed that there was a significant difference for number of correct shades matched by two observer groups. Percentage of correctly matched shades by instrumental evaluation was 37%. Good visual-instrumental shade agreement was observed. Conclusions: The present study concluded that there was significant difference for number of correct shades matched by two observer groups - DP and NP. Good visual-instrumental agreement was found.